Environmental impact of corruption risks in the field of land relations - R. Mykolaenko; O. Hulak; L. Holoviy; A. Shcherbak (Law. Human. Environment, 2025)
The relevance of this subject is caused by the fact that the analysis of corrup- tion risks in the field of land relations allows identifying real shortcomings and gaps in the current legislation. If these problems are left unresolved, it will contribute to the further development of corruption in Ukraine, which is an agrarian country. Elimi- nating these risks is a key step towards ensuring transparency and effective land management, which is crucial for the country’s sustainable development. The purpose of this study was to provide a compre- hensive analysis of the effects of corruption risks identified in strategic anti-corruption legislation on the environment. The study employed the following methods: systemic and structural, formal-logical, and comparative. The findings of the study indicated that corruption in the field of land relations is a global problem typical for many countries, including Ukraine. The study found that corruption in this area leads to irrational use of land, which adversely affects the agrarian potential of the state. The study emphasised the need to introduce effective measures to minimise corruption risks, namely: replacing the procedure of free privatisation of land plots with alternative forms of social support for the popu- lation; establishing clear market-based rental rates for state and communal land; and completing the necessary stages for a full transition to electronic registration of land plots. It was concluded that the fight against corruption in the field of land relations should be considered not only as an economic pri- ority, but also as a critical tool for environmental protection. The study of corruption risks in the field of land relations and their effects on the environment is of great practical significance for the development of anti-corruption mechanisms, ensuring transparency of land use and protection of ecological balance. Its findings will help to improve legal regulation, introduce public control, and minimise the negative environmental consequences of illegal use of land resources